2020
DOI: 10.15690/vsp.v19i6.2152
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Transcutaneous Sensitization to Cow Milk Proteins in Infants with Atopic Dermatitis: Cohort Study

Abstract: Background. Malformations in epidermal barrier in children with atopic dermatitis (AD) can cause transcutaneous sensitization with further development of allergic diseases that can worsen the AD course and significantly reduces patients’ quality of life.Objective. The aim of the study was to determine the effect of topical treatment and maintenance therapy with pimecrolimus 1% cream (PIM) and topical glucocorticosteroids (tGCS) in infants with AD on reducing the risk of developing transcutaneous sensitization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The proactive group experienced significant reductions in AD severity, quality of life scores, and serum TARC levels compared with the reactive group. Another observational study found that infants aged 1–4 months who received active eczema treatment with topical glucocorticoids for 10 days followed first by maintenance therapy with pimecrolimus 1% cream twice daily for 3 months, and continued on pimecrolimus twice daily three times a week until age 1 year had a lower risk of food allergen sensitization compared with infants who received only reactive treatment with topical steroids during eczema flares 58 . A retrospective study by Miyaji et al 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The proactive group experienced significant reductions in AD severity, quality of life scores, and serum TARC levels compared with the reactive group. Another observational study found that infants aged 1–4 months who received active eczema treatment with topical glucocorticoids for 10 days followed first by maintenance therapy with pimecrolimus 1% cream twice daily for 3 months, and continued on pimecrolimus twice daily three times a week until age 1 year had a lower risk of food allergen sensitization compared with infants who received only reactive treatment with topical steroids during eczema flares 58 . A retrospective study by Miyaji et al 7 .…”
Section: Introductionmentioning
confidence: 99%